Assessment of TAPI's role in the transfer of technologies from the universities to business firms - Lazcano, Joy M.; Posadas, Roger D. (Quezon City University of the Philippines Diliman, 2014)
Starting the year 1996 up to the present, the Technology Application and Promotions Institute of the Department of Science and Technology conducts annual national invention contests to amateur and professional grassroots inventors. Previously, the invention contest was called as the National Invention Week (NIW) before it was later named as the National Inventions Contests and Exhibits (NICE), a weeklong invention contests for young and professional inventors held every third week of November by virtue of Republic Act 7259 or the Filipino Inventors Incentives. Moreover, both NIW and NICE were able to generate a huge number of invention entries both from the academic and professional inventors and researchers annually. However, with the number of knowledge generated in the invention contests every year, it is postulated that the number of such inventions and researches hardly reach the commercial stage. It is argued that most of these inventions have low commercial viability and worst, quality. At the present, companies that seek to commercialize their technologies face a dynamic set of challenges, attitudes and values. The demand for better, faster, cheaper technology products is a dilemma that a few companies have successful overcome. Intellectual property, once a cost center for most corporations, has now become an important revenue center- a critical competitive advantage for the firms that hold it and a significant disadvantage for those that do not. Incremental innovation-improving on what has already been done-has traditionally helped a company survive and compete. Vijay Jolly postulated that "technology commercialization, in other words, is about performing successfully a range of things, each adding value to the technology as it progresses. Also, UP TMC Professor Roger Posadas pushes the following steps in considering the commercializability of the invention : Ease of Commercialization, addressing a pending problem, resources available in niche, downstream barriers to commercialization, readiness of technology for application. Uniqueness of Application, most cost effective solution, unique technical solution. Scope of Problems Addressed, helps expand product scope, helps expand the core technology and widens patent coverage. And with the complexity in today's technology and commercialization, the vertical transfer of technology framework is still the more appropriate methodology in commercializing technology and inventions in the embryonic stage. The transfer of an embryonic technology (i.e., a pre-commercialized or generic technology) from an individual or institutional inventor (e.g. a government or university laboratory) to an organization that can either commercialize it into a new product or process to make it publicly available for the practical solution of a problem in society. The Technology Application and Promotion Institute of the Department of Science and Technology annually sponsors invention contests that features research and inventions from the lower level of education up to the professional inventors. Previously, the National Invention Week (NIW) was an annual competition of local inventors and researchers that features various inventions from basic research, utility model, inventions and industrial design. In later years, NIC was superseded by the National Invention Contests and Exhibits (NICE).
In partial fulfillment of the requirements in TM 299
Thesis
Keywords: Technology Application and Promotions Institute (TAPI); Philippines. Department of Science and Technology; Technology transfer